The Composite Nature of Dust-obscured Galaxies (DOGs) at z ∼ 2–3 in the COSMOS Field. II. The AGN Fraction - Riguccini, Laurie A.; Treister, Ezequiel; Menéndez-Delmestre, Karin; Cardamone, Carolin; Civano, Francesca; Gonçalves, Thiago S.; Hasinger, Guenther; Koekemoer, Anton M.; Lanzuisi, Giorgio; Floc’h, Emeric Le; Lusso, Elisabeta; Lutz, Dieter; et al. (Astronomical Journal, 2019)
We present the X-ray properties of 108 Dust-Obscured Galaxies (DOGs; F 24 μm/F R > 1000) in the COSMOS field, all of which are detected in at least three far-infrared bands with the Herschel Observatory. Out of the entire sample, 22 are individually detected in the hard 2–8 keV X-ray band by the Chandra COSMOS Legacy survey, allowing us to classify them as AGN. Six (27%) of them are Compton-thick AGN candidates with column densities N H > 1024 cm−2, while 15 are moderately obscured AGNs with 1022 < N H < 1024 cm−2. Additionally, we estimate AGN contributions to the IR luminosity (8–1000 μm rest-frame) greater than 20% for 19 DOGs based on SED decomposition using Spitzer/MIPS 24 μm and the five Herschel bands (100–500 μm). Only 7 of these are detected in X-rays individually. We performed an X-ray stacking analysis for the 86 undetected DOGs. We find that the AGN fraction in DOGs increases with 24 μm flux and that it is higher than that of the general 24 μm population. However, no significant difference is found when considering only X-ray detections. This strongly motivates the combined use of X-ray and far-IR surveys to successfully probe a wider population of AGNs, particularly for the most obscured ones.
EPrint Processing Status: Full text deposited in DRO
Keywords: Centre for Extragalactic Astronomy